PENINGKATAN KUALITAS HIDUP DAN KESEHATAN MASYARAKAT KELOMPOK RENTAN PASCA BENCANA BANJIR BANDANG DI KENAGARIAN PANDAI SIKEK - Markolinda, Yessy; Ramadani, Mery; Augia, Trisfa; Novirsa, Randy; Elda, Frima; Kasra, Kamal; Husna, Nadiyatul; Aurora, Bunga Putri; Efendi, Melati Putria; Deca, Fathiya Zarine; Cahyani, Mardhiah BP (Warta Pengabdian Andalas, 2025)
Nagari Pandai Sikek West Sumatra experienced a flash flood disaster that caused infrastructure damage, disruption of basic services, and decreased the quality of life of the community, especially vulnerable groups. This activity aims to improve the quality of life and health of post-disaster communities through an integrated approach in the fields of health and disaster management. The quality of life of the community is measured through a composite approach that includes knowledge improvement (pre- and post-tests), behavioral changes and participation in activities, simple health conditions (blood pressure and physical activity), waste bank and maggot-based environmental management, and community social involvement. These indicators show improvements in physical, cognitive, social, and environmental aspects after the community service activities. Activity methods include socialization, simulation, and education with a pre-test and post-test approach to measure the effectiveness of the intervention. Activities were carried out in the form of disaster mitigation counseling for elementary school students, maggot-based waste management training, healthy lifestyle counseling for the elderly through the GERMAS program, and nutrition education for parents related to stunting prevention. The results of the activity showed an increase in public understanding of disaster mitigation, with an average pre-test score of 58.4 increasing to 82.7 in the post-test. The community demonstrated a better understanding of the importance of waste management to prevent environmental pollution, awareness of early detection of hypertension, and the fulfillment of balanced nutrition to prevent stunting. Active participation in simulations, question and answer sessions, and discussions were indicators of the success of the activity. It can be concluded that this community service program succeeded in increasing the understanding and awareness of the Pandai Sikek community regarding health and disaster preparedness. The sustainability of this program needs to be supported through collaboration with local governments, educational institutions, and local communities to expand its positive impact.